2021
DOI: 10.1126/sciadv.abl6432
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-scavenging nanodecoys reconstruct osteoclast/osteoblast balance toward the treatment of postmenopausal osteoporosis

Abstract: Biomimetic nanodecoys reconstruct the osteoclast/osteoblast balance to treat postmenopausal osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 59 publications
1
47
0
Order By: Relevance
“…ZIA is an acute inflammatory arthritis model which involves both acute inflammation and excessive T cell activation [ 18b,19a,26 ] It will cause severe tissue damage, and thus it is important to reduce inflammation quickly and effectively. We first determined the anti‐inflammatory efficacy of PRM NDs in ZIA mice by monitoring the expression levels of pro‐inflammatory cytokines in the synovium tissues of ZIA mice at day 6 post i.v.…”
Section: Resultsmentioning
confidence: 99%
“…ZIA is an acute inflammatory arthritis model which involves both acute inflammation and excessive T cell activation [ 18b,19a,26 ] It will cause severe tissue damage, and thus it is important to reduce inflammation quickly and effectively. We first determined the anti‐inflammatory efficacy of PRM NDs in ZIA mice by monitoring the expression levels of pro‐inflammatory cytokines in the synovium tissues of ZIA mice at day 6 post i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Given the multifunctional effects of bioactive ions reported to comodulate the pro-osteogenic and anti-osteoclastogenic healing processes 18 , 20 , 49 51 and the previously reported role of Mo in promoting periodontal regeneration, 29 in this study, we further investigated the therapeutic effect of Mo ions from the standpoint of orchestrating the cellular responses of osteoblasts and osteoclasts using in vitro and in vivo models. Previously, we found that a strut-packed Mo-containing bioactive glass ceramic scaffold with a hollow-pipe structure can promote periodontal wound healing; 29 however, the hollow-pipe structure can cause unnecessary infection due to the poor filling of newly formed bone.…”
Section: Discussionmentioning
confidence: 99%
“…at the first day of each week. Micro-CT analyses were described in an early study [ 70 ]. In brief, the OVX mice and the control mice were scanned under the micro-CT equipment (Skyscan 1176, Belgium) 8 weeks after OVX procedure and the high-resolution scanogram were retrieved [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…Micro-CT analyses were described in an early study [ 70 ]. In brief, the OVX mice and the control mice were scanned under the micro-CT equipment (Skyscan 1176, Belgium) 8 weeks after OVX procedure and the high-resolution scanogram were retrieved [ 70 ]. The dataset was reconstructed under a CT analyzer software and bone erosion was calculated using the in-house Fiji script [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation